Front Cover: Synthesis and Properties of the Octaboron Cluster Series hypercloso‐B8Cl8, the Radical Anion hypercloso‐[B8Cl8].− and the Dianion closo‐[B8Cl8]2− (Eur. J. Inorg. Chem. 48/2021). Issue 48 (8th December 2021) - Einholz, Wolfgang; Hofmann, Matthias; Schäfer, Ronald; Wieloch, Christoph; Keller, Willi; Ströbele, Markus; Meyer, Hans‐Jürgen
Abstract : The Front Cover shows the redox scheme of the octaborane cluster series hypercloso ‐B8 Cl8, hypercloso ‐[B8 Cl8 ] −, and closo ‐[B8 Cl8 ] 2− . Neutral B8 Cl8 – a dark green solid – has in its polyhedrons only 2 n = 16 framework electrons instead of 2 n + 2 = 18, as the closo ‐clusters should have according to the rules of Wade. Consequently, B8 Cl8 is a strong oxidant and easily adopts an electron, giving the intense purple colored radical anion [B8 Cl8 ] −, which can also be easily reduced to the more stable dianion closo ‐[B8 Cl8 ] 2− . This closo ‐cluster has a D2d dodecahedral molecular structure in the solid state, but in solution it shows a highly fluxional mobility. More information can be found in the Full Paper by W. Einholz and co‐workers .